1993
DOI: 10.1002/aic.690391017
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the reaction of carbon dioxide with aqueous 2‐piperidineethanol solutions

Abstract: Sterically hindered amines have been proposed recently as attractive solvents for acid gas purification, since they have not only greater capacity for C 0 2 but also a low tendency to form carbamate and an appreciable absorption rate for C 0 2 (Sharma, 1965;Sartori and Savage, 1983;Savage et al., 1984;Say et al., 1984). The advantages of sterically hindered amines result from the bulkiness of the substituent attached to the amino group which causes an increased cyclic capacity and a decreased energy consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 16 publications
5
26
2
Order By: Relevance
“…Plots of log R CO2 = ½CO 2 Ã ffiffiffiffiffiffiffiffiffiffi D CO2 p À Á È É versus log [PE] at 298, 303, and 308 K are shown in Figure 7. Our k 2 value at T ¼ 303 K is close to that reported by Xu et al [23] From the dependence of our values of k 2 on temperature, the activation energy was found to be 54.2 kJ/mol (see Figure 8). The slope equals 0.51, 0.51, and 0.55 thereby suggesting that the reaction order with respect to PE is close to unity (viz., 1.02-1.1).…”
Section: Co 2 -Pe Reaction Systemsupporting
confidence: 90%
See 1 more Smart Citation
“…Plots of log R CO2 = ½CO 2 Ã ffiffiffiffiffiffiffiffiffiffi D CO2 p À Á È É versus log [PE] at 298, 303, and 308 K are shown in Figure 7. Our k 2 value at T ¼ 303 K is close to that reported by Xu et al [23] From the dependence of our values of k 2 on temperature, the activation energy was found to be 54.2 kJ/mol (see Figure 8). The slope equals 0.51, 0.51, and 0.55 thereby suggesting that the reaction order with respect to PE is close to unity (viz., 1.02-1.1).…”
Section: Co 2 -Pe Reaction Systemsupporting
confidence: 90%
“…[21] The CO 2 reaction with PE is faster than that with MDEA, according to Shen et al [22] Their value of the second-order rate constant is equal to 195 m 3 / (kmol s) at 313 K. The value published in Xu et al [23] is much higher (1468 m 3 /(kmol s)). It is a promising candidate absorbent for CO 2 capture in terms of both absorption capacity and kinetics.…”
Section: Introductionmentioning
confidence: 96%
“…Accurate measurement of vapor-liquid-equilibrium (VLE) and absorption/desorption rates was made possible by using a wetted wall column, which better represents mass transfer between gas and liquid in real packing. Although some thermodynamic or kinetic studies had been reported for some of the amines (Xu et al, 1993;Paul et al, 2009a,b), the amine concentration in this study is much higher (>3 kmol/m 3 ), close to the practical range that is most interesting for industrial application. The concentration for aqueous amine solution is expressed in molality (m, mol amine/kg water) throughout this paper.…”
Section: Introductionmentioning
confidence: 78%
“…2-PE is a hindered amine because of the hydroxyethyl group attached to amino group, so there forms no or very little carbamate as 2-PE reacts with CO 2 (Sartori and Savage, 1983). The second order reaction rate constant (k 2 ) of 2-PE with CO 2 was reported by Xu et al (1993) to be 0.6 m 3 /mol s, which is two orders of magnitude smaller than the value for PZ of 54 m 3 /mol s (Bishnoi and Rochelle, 2000). However, 2-PE is not considerably slower than PZ as what would be expected from the k 2 values.…”
Section: -Pementioning
confidence: 97%
“…In the extensive field of gas treating, alkanolamines have become one of the most important classes of chemicals for the removal of CO 2 . Sterically hindered amines such as 2-amino-2-methyl-1-propanol (AMP), 2-piperidineethanol (2-PE) have been proposed as commercially attractive new solvents for acid gas treating over conventional amines such as monoethanolamine (MEA), diethanolamine (DEA), di-2-propanolamine (DIPA) and Nmethyldiethanolamine (MDEA) [3][4][5][6][7][8][9][10][11][12]. The advantages of these sterically hindered amines are mainly due to their particular structure which results in increased cyclic capacity and thermodynamic capacity for CO 2 absorption.…”
Section: Introductionmentioning
confidence: 99%